Why Whip the Starving Horse When There Are Oats for the Starving Myocardium?. (September 2016) - Fürstenwerth, Hauke
Abstract : Digoxin is the oldest drug for treatment of heart failure still in clinical use. Despite over 200 years of clinical experience with this drug, the optimal serum concentration required for both efficacy and safety remains unknown. It has been suggested that low doses have more favorable effects than higher ones. Cardiac glycosides act on the Na/K-ATPase (NKA). They show an inverted U-shaped dose–response curve with inhibition of pumping at high concentrations while increasing NKA activity at low concentrations. The classical sigmoidal dose–response curve describing an inhibition of the NKA by cardiac glycosides cannot explain this stimulatory effect. Cardiac glycosides are prototypical examples of hormetic substances. Biphasic dose–response curves of cardiac glycosides are also found in their neurohormonal effects. In low concentrations, vagomimetic effects are observed, whereas in high concentrations, sympathomimetic effects dominate. Lipophilic Digitalis glycosides have greater sympathomimetic effects; hydrophilic Strophanthus glycosides have greater vagomimetic effects. For digoxin, as a strong inotrope, there is evidence of only weak modulation of the autonomic nervous system. In ouabain, the modulation of the autonomic nervous system prevails over weak inotropic effects. Vagomimetic and sympatholytic effects characterize the therapeutic effects. In contrast to those of digoxin, the therapeutic effects of ouabain follow exactly the measurable serum concentration. Contrary to common prejudice ouabain is suitable for oral administration. Timely adjustments of dosage to patient therapeutic needs are easy to achieve with orally administered ouabain. Ouabain has the potential to crucially improve our arsenal of heart failure medications. Therefore, a clinical re-evaluation of ouabain is warranted. Randomized double-blind prospective clinical studies with ouabain, which meet today's standards, are worthwhile and necessary.